Plugging agent and preparation method thereof
By using water-based drilling fluid sealing agent composed of emulsifiers, etc., the synergistic effect of AuNPs/PNIPAM gel composite and polybutadiene is used to solve the problem of poor effect of existing sealing agents at high temperatures, and efficient intelligent sealing and long-life drilling fluid performance are achieved.
Patent Information
- Application Number
- CN202311471750.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-05-09
AI Technical Summary
The existing water-based drilling fluid sealing agent is not effective at the micro-nano-scale pores and joints of mud shale, and the sealing effect of flexible materials is affected by temperature, and the reservoir protection and environmental protection performance are poor, which affects the performance of drilling fluid.
The sealing agent composed of emulsifier, temporary plugging agent, AuNPs/PNIPAM gel composite, monomer, initiator, viscosist, dispersant, defoaming agent, base liquid and antifreeze are prepared through specific mixing and drying steps to form composite particles with synergistic effects.
At high temperature, the synergistic effect of AuNPs/PNIPAM and polybutadiene improves the temperature resistance and sealing effect of the sealing agent, realizes intelligent sealing, extends the recycling rate of the sealing agent, and maintains the stability of the drilling fluid performance.
Smart Images

Figure BDA0004535357650000071 
Figure BDA0004535357650000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas development drilling, in particular to a plugging agent for water-based drilling fluid. Background Art
[0002] With the increasing complexity of drilling strata for oil and gas development, the problem of wellbore instability in shale formations, coal seams, loose seabeds, deep formations, etc. has become increasingly prominent. The wellbore instability caused by the development of microcracks in shale formations accounts for more than 65% of the complex situations, which seriously restricts the speed and efficiency of drilling. Due to the heterogeneity of shale and the multi-size characteristics of microcracks, it is necessary to develop adaptive plugging agents for water-based drilling fluids to improve the plugging performance of water-based drilling fluids, prevent or delay the intrusion of drilling fluids, and solve the technical problems of wellbore instability. At present, water-based drilling fluid plugging agents are rigid materials, flexible materials, or a combination of the two.
[0003] However, at the micro-nanoscale pores and fractures of shale, the particle size grading conditions for rigid materials are more stringent, while flexible plugging materials face problems such as the plugging effect being restricted by temperature (softening point / cloud point), poor reservoir protection and environmental protection performance, and impact on drilling fluid performance. Summary of the invention
[0004] One of the present inventions provides a plugging agent, the raw materials of which include an emulsifier, a temporary plugging agent, an AuNPs / PNIPAM gel complex, a monomer, an initiator, a viscosity agent, a dispersant, a defoaming agent, a base liquid and an optional antifreeze agent.
[0005] In a specific embodiment, the emulsifier is 5 to 6 parts by mass, the temporary plugging agent is 5 to 10 parts by mass, the AuNPs / PNIPAM gel complex is 45 to 55 parts by mass, the monomer is 5 to 8 parts by mass, the initiator is 3 to 6 parts by mass, the viscosity agent is 5 to 6 parts by mass, the dispersant is 2 to 3 parts by mass, the defoamer is 1 to 2 parts by mass, the antifreeze agent is 0 to 4 parts by mass, and the base liquid is 10 to 20 parts by mass.
[0006] In a specific embodiment, the antifreeze agent is 2 to 4 parts by mass.
[0007] In a specific embodiment, the emulsifier is sodium hydroxypropane sulfonate methacrylate.
[0008] In a specific embodiment, the temporary plugging agent is a polymer synthesized from butadiene, styrene, and 2-acrylamido-2-methylpropanesulfonic acid in a mass percentage of 3:1:1.
[0009] In one embodiment, the monomer is butadiene.
[0010] In a specific embodiment, the initiator is azobisisobutylamidine dihydrochloride.
[0011] In a specific embodiment, the thickening agent is xanthan gum.
[0012] In one embodiment, the dispersant is a nano-silicon dioxide dispersion, and the particle size of the nano-silicon dioxide dispersion is in the range of 15 to 100 nm. 90 Less than 90nm, solid content 25wt%.
[0013] In a specific embodiment, the defoaming agent is a higher alcohol fatty acid ester and / or polydimethylsiloxane, for example, a composition of a higher alcohol fatty acid ester and polydimethylsiloxane in a mass ratio of 1:1.
[0014] In a specific embodiment, the antifreeze agent is ethylene glycol and / or glycerol, for example, a composition of ethylene glycol and glycerol in a mass ratio of 1:1.
[0015] In one embodiment, the base fluid is water.
[0016] The second aspect of the present invention provides a method for preparing the plugging agent according to the first aspect of the present invention, which comprises the following steps:
[0017] 1) mixing an emulsifier with a base liquid to obtain a first mixed liquid;
[0018] 2) mixing the first mixed liquid with a temporary plugging agent to obtain a second mixed liquid;
[0019] 3) mixing the second mixed solution with the AuNPs / PNIPAM gel complex to obtain a third mixed solution;
[0020] 4) mixing the third mixed liquid with butadiene to obtain a fourth mixed liquid;
[0021] 5) mixing the fourth mixed solution with an initiator to obtain a fifth mixed solution;
[0022] 6) mixing the fifth mixed liquid with a thickener, a dispersant, a defoaming agent and an antifreeze agent to obtain a sixth mixed liquid;
[0023] 7) filtering the sixth mixed solution to obtain a filtrate;
[0024] 8) Drying the filtrate to obtain the plugging agent.
[0025] In a specific embodiment, in step 1), stirring is performed at 30 to 50° C. at a rotation speed of 60 to 120 r / min for 5 to 7 min to mix uniformly.
[0026] In a specific embodiment, in step 2) to step 4), stirring and mixing are independently carried out at 30 to 50° C. and 4500 to 6000 r / min for 10 to 35 min.
[0027] In one specific embodiment, in step 5), the initiator is added to the fourth mixed solution at 70 to 90° C., and the mixture is reacted for 25 to 45 minutes at a stirring speed of 120 r / min or less at a temperature of 50 to 70° C. For example, the mixture is reacted for 25 to 45 minutes at a stirring speed of 100 to 120 r / min at a temperature of 50 to 70° C.
[0028] In a specific embodiment, in step 6), the fifth mixed solution is mixed with a thickener, a dispersant, a defoamer and an antifreeze agent under stirring at 50 to 70° C., and stirring is continued at 70 to 90° C. for 1 to 2 hours.
[0029] In a specific embodiment, in step 8), after stirring the filtrate for 3 to 5 minutes, the filtrate is dried by vacuum drying at 75 to 85° C. for 8 to 10 hours.
[0030] The third aspect of the present invention provides the use of the plugging agent described in the first aspect of the present invention or the plugging agent prepared by the method described in the second aspect of the present invention as a component in a water-based drilling fluid.
[0031] In a specific embodiment, the application is an application for plugging a formation at a formation temperature of 80 to 130°C.
[0032] Beneficial effects of the present invention:
[0033] In the plugging agent of the present invention, AuNPs / PNIPAM and polybutadiene show synergistic effect at high temperature, and the synergistic effect of AuNPs / PNIPAM and polybutadiene can make up for the problem of decreased permeability reduction rate caused by using both alone at higher temperatures, showing temperature resistance. Based on the characteristics of the plugging agent of the present invention, it can play a role according to different formation temperatures downhole, that is, when the drilling fluid circulates to the ground, the plugging effect is weak when it is lower than the response temperature; when the drilling fluid circulates to the underground, the plugging is strong when it reaches the response temperature and above, thereby realizing intelligent plugging and improving the recycling rate of the plugging agent, maintaining the stable performance of the drilling fluid. In addition, the preparation method of the plugging agent of the present invention has controllable reaction conditions, simple operation, convenient processing and production, and is suitable for promotion and application. DETAILED DESCRIPTION
[0034] The above contents of the present invention are further described in detail below in the form of preferred implementation cases, but they do not constitute a limitation to the present invention.
[0035] Unless otherwise specified, the reagents in the embodiments of the present invention can be purchased through commercial channels.
[0036] Gold nanoparticles / poly (N-isopropylacrylamide) gel composites (AuNPs / PNIPAM, or PNIPAM-AuNPs) were purchased from Xi'an Ruixi Biotechnology Co., Ltd.
[0037] The temporary sealing agent is a polymer synthesized from butadiene, styrene and 2-acrylamide-2-methylpropanesulfonic acid in a mass percentage of 3:1:1.
[0038] The initiator was azobisisobutylamidine dihydrochloride (AIBA), purchased from Tangshan Chenhong Industrial Co., Ltd., model CHV50, with a purity of 97%.
[0039] Nano-silicon dioxide dispersion, with a solid content of 25wt%, nano-silicon dioxide particle size ranging from 15 to 100nm, D 90 Less than 90nm.
[0040] High carbon alcohol fatty acid esters were purchased from Hubei Chengfeng Chemical Industry.
[0041] Polydimethylsiloxane was purchased from Aladdin, product number H431357-50ml).
[0042] Example 1
[0043] 1) adding 5 parts by mass of an emulsifier sodium methacrylate hydroxypropane sulfonate and 20 parts by mass of water into a stirring container, stirring at a temperature of 30° C. and a speed of 120 r / min for 5 minutes, and mixing evenly to obtain a first mixed solution;
[0044] 2) adding 10 parts by mass of temporary plugging agent to the first mixed solution under stirring at 30°C and 4500 r / min, stirring for 10 minutes, mixing evenly, and obtaining a second mixed solution;
[0045] 3) adding 45 parts by mass of AuNPs / PNIPAM gel complex to the second mixed solution under stirring at 30° C. and 4500 r / min, and mixing well to obtain a third mixed solution;
[0046] 4) adding 5 parts by mass of butadiene to the third mixed solution under stirring at 30° C. and 4500 r / min, and continuously stirring at 30° C. and 5200 r / min for 30 min to obtain a fourth mixed solution;
[0047] 5) adding a total of 3 parts by mass of an initiator azobisisobutylamidine dihydrochloride to the fourth mixed solution in small amounts and multiple times at a temperature of 70° C. After all the initiators are added, stirring the mixture at a temperature of 50° C. and a speed of 120 r / min for 25 min to obtain a fifth mixed solution;
[0048] 6) at a temperature of 50° C., under stirring, 6 parts by mass of a thickener xanthan gum, 2 parts by mass of a nano-silicon dioxide dispersion, 1 part by mass of a defoamer high-carbon alcohol fatty acid ester, and 3 parts by mass of an antifreeze agent (a composition of ethylene glycol and glycerol in a mass ratio of 1:1) were added to the fifth mixed solution in sequence, and the added thickener, dispersant, defoamer, and antifreeze agent were uniformly mixed by stirring. After all of them were added, stirring was continued at a temperature of 50° C. for 1 hour to obtain a sixth mixed solution;
[0049] 7) filtering the sixth mixed solution using a microporous filter membrane with a pore size of 0.22 μm, and repeating the filtration three times to obtain a filtrate;
[0050] 8) Stir the filtrate with a stirring rod for 3 minutes, place the filtrate in a vacuum drying oven, and continue drying at 75° C. for 8 hours to obtain a water-based drilling fluid adaptive plugging agent.
[0051] Example 2
[0052] 1) adding 5 parts by mass of an emulsifier sodium methacrylate hydroxypropane sulfonate and 10 parts by mass of water into a stirring container, stirring at a temperature of 40° C. and a speed of 90 r / min for 6 minutes to mix evenly to obtain a first mixed solution;
[0053] 2) adding 8 parts by mass of temporary plugging agent to the first mixed solution under stirring at 40°C and 5000 r / min, stirring for 30 minutes, mixing evenly, and obtaining a second mixed solution;
[0054] 3) adding 50 parts by mass of AuNPs / PNIPAM gel complex to the second mixed solution under stirring at 40° C. and 5000 r / min, and mixing well to obtain a third mixed solution;
[0055] 4) adding 7 parts by mass of butadiene to the third mixed solution under stirring at 40° C. and 5000 r / min, and continuously stirring at 40° C. and 5000 r / min for 33 min to obtain a fourth mixed solution;
[0056] 5) adding 5 parts by weight of initiator azobisisobutylamidine dihydrochloride to the fourth mixed solution in small amounts and multiple times at a temperature of 90° C. After all the initiators are added, stirring is continued at a temperature of 60° C. and a speed of 100 r / min for 30 min to obtain a fifth mixed solution;
[0057] 6) adding 6 parts by mass of a thickener xanthan gum, 3 parts by mass of a nano-silicon dioxide dispersion, 2 parts by mass of a defoamer polydimethylsiloxane, and 4 parts by mass of an antifreeze agent ethylene glycol to the fifth mixed solution in sequence at a temperature of 60° C. and under stirring, the added thickener, dispersant, defoamer, and antifreeze agent are uniformly mixed by stirring, and after all are added, stirring is continued at a temperature of 60° C. for 1.5 hours to obtain a sixth mixed solution;
[0058] 7) filtering the sixth mixed solution using a microporous filter membrane with a pore size of 0.22 μm, and repeating the filtration three times to obtain a filtrate;
[0059] 8) Stir the filtrate with a stirring rod for 5 minutes, place the filtrate in a vacuum drying oven, and continue drying at 80° C. for 9 hours to obtain a water-based drilling fluid adaptive plugging agent.
[0060] Example 3
[0061] 1) adding 6 parts by mass of an emulsifier sodium methacrylate hydroxypropane sulfonate and 10 parts by mass of water into a stirring container, stirring at a temperature of 50° C. and a speed of 60 r / min for 7 minutes, and mixing evenly to obtain a first mixed solution;
[0062] 2) Add 5 parts by mass of temporary plugging agent to the first mixed solution under stirring at 50°C and 6000 r / min, stir for 35 minutes, mix well, and obtain a second mixed solution;
[0063] 3) adding 55 parts by mass of AuNPs / PNIPAM gel complex to the second mixed solution under stirring at 50° C. and 6000 r / min, and mixing well to obtain a third mixed solution;
[0064] 4) adding 8 parts by mass of butadiene to the third mixed solution under stirring at 50° C. and 6000 r / min, and continuously stirring at 60° C. and 6000 r / min for 35 min to obtain a fourth mixed solution;
[0065] 5) adding 6 parts by weight of initiator azobisisobutylamidine dihydrochloride to the fourth mixed solution in small amounts and multiple times at a temperature of 80° C. After all the initiators are added, stirring is continued at a temperature of 70° C. and a speed of 100 r / min for 45 min to obtain a fifth mixed solution;
[0066] 6) at a temperature of 70° C., under stirring, 5 parts by mass of a thickener xanthan gum, 2 parts by mass of a nano-silicon dioxide dispersion, 1 part by mass of a defoamer (a composition of a high-carbon alcohol fatty acid ester and polydimethylsiloxane in a mass ratio of 1:1), and 2 parts by mass of an antifreeze agent glycerol were sequentially added to the fifth mixed solution, and the added thickener, dispersant, defoamer, and antifreeze agent were uniformly mixed by stirring. After all of them were added, stirring was continued at a temperature of 70° C. for 2 hours to obtain a sixth mixed solution;
[0067] 7) filtering the sixth mixed solution using a microporous filter membrane with a pore size of 0.22 μm, and repeating the filtration three times to obtain a filtrate;
[0068] 8) Stir the filtrate with a stirring rod for 3 minutes, place the filtrate in a vacuum drying oven, and continue drying at 85° C. for 10 hours to obtain a water-based drilling fluid adaptive plugging agent.
[0069] Comparative Example 1
[0070] Omit step 3) in Example 2, and the specific operations are as follows:
[0071] 1) adding 5 parts by mass of an emulsifier sodium methacrylate hydroxypropane sulfonate and 10 parts by mass of water into a stirring container, stirring at a temperature of 40° C. and a speed of 90 r / min for 6 minutes to mix evenly to obtain a first mixed solution;
[0072] 2) adding 8 parts by mass of temporary plugging agent to the first mixed solution under stirring at 40°C and 5000 r / min, stirring for 10 minutes, and mixing evenly to obtain a second mixed solution;
[0073] 3) adding 7 parts by mass of butadiene to the second mixed solution under stirring at 40° C. and 5000 r / min, and continuously stirring at 40° C. and 5000 r / min for 33 min to obtain a third mixed solution;
[0074] 4) adding 5 parts by weight of initiator azobisisobutylamidine dihydrochloride to the third mixed solution in small amounts and multiple times at a temperature of 90° C. After all the initiators were added, stirring was continued at a temperature of 60° C. and a speed of 100 r / min for 30 min to obtain a fourth mixed solution;
[0075] 5) at a temperature of 60° C., under stirring, 6 parts by mass of a thickener xanthan gum, 3 parts by mass of a nano-silicon dioxide dispersion, 2 parts by mass of a defoaming agent polydimethylsiloxane, and 4 parts by mass of an antifreeze agent ethylene glycol were sequentially added to the fourth mixed solution, the thickener, dispersant, defoaming agent, and antifreeze agent were uniformly mixed by stirring, and after all were added, stirring was continued at a temperature of 60° C. for 1.5 hours to obtain a fifth mixed solution;
[0076] 6) filtering the fifth mixed solution using a microporous filter membrane with a pore size of 0.22 μm, and repeating the filtration three times to obtain a filtrate;
[0077] 7) Stir the filtrate with a stirring rod for 5 minutes, place the filtrate in a vacuum drying oven, and continue drying at 80° C. for 9 hours to obtain a water-based drilling fluid adaptive plugging agent.
[0078] Comparative Example 2
[0079] Omit step 4) and step 5) in Example 2, and the specific operations are as follows:
[0080] 1) adding 5 parts by mass of an emulsifier sodium methacrylate hydroxypropane sulfonate and 10 parts by mass of water into a stirring container, stirring at a temperature of 40° C. and a speed of 90 r / min for 6 minutes to mix evenly to obtain a first mixed solution;
[0081] 2) adding 8 parts by mass of temporary plugging agent to the first mixed solution under stirring at 40°C and 5000 r / min, stirring for 10 minutes, and mixing evenly to obtain a second mixed solution;
[0082] 3) adding 50 parts by mass of AuNPs / PNIPAM gel complex to the second mixed solution under stirring at 40° C. and 5000 r / min to obtain a third mixed solution;
[0083] 4) adding 6 parts by mass of xanthan gum as a thickener, 3 parts by mass of a nano-silicon dioxide dispersion, 2 parts by mass of a defoaming agent, and 4 parts by mass of an antifreeze agent, ethylene glycol, to the third mixed solution in sequence under stirring at a temperature of 60° C., the added thickener, dispersant, defoaming agent, and antifreeze agent are uniformly mixed by stirring, and after all are added, stirring is continued at a temperature of 60° C. for 1.5 hours to obtain a fourth mixed solution;
[0084] 5) filtering the fourth mixed solution using a microporous filter membrane with a pore size of 0.22 μm, and repeating the filtration three times to obtain a filtrate;
[0085] 6) Stir the filtrate with a stirring rod for 5 minutes, place the filtrate in a vacuum drying oven, and continue drying at 80° C. for 9 hours to obtain a water-based drilling fluid adaptive plugging agent.
[0086] Comparative Example 3
[0087] The AuNPs / PNIPAM gel complex in Example 2 was replaced with a dispersion of ferroferric oxide nanoparticles with a particle size of 50 to 150 nm (purchased from Aladdin, item number I298919, wherein the content of ferroferric oxide nanoparticles was 20 wt %, and the amount of ferroferric oxide nanoparticles was 50 parts by mass), and the rest was the same as in Example 2.
[0088] Test Example 1
[0089] Water-based drilling fluid: 4wt% sodium bentonite + 0.5wt% viscosity enhancer + 1.5wt% fluid loss reducer + 0.5wt% inhibitor + 2wt% polyol + 3wt% plugging agent + 100wt% water, wherein the sodium bentonite complies with GB5005 standard; the viscosity enhancer complies with SY / T5661 industry standard; the fluid loss reducer is SMP-2 type resin purchased from Shunyuan Petroleum Technology Co., Ltd.; the inhibitor is polyol purchased from Shunyuan Petroleum Technology Co., Ltd.; the plugging agents are the plugging agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively.
[0090] Core preparation: in accordance with the requirements of SY / T 5613 for shale sample sources, core permeability <10×10 -3 μm 2 ; Drill a cylindrical sample with a diameter of 25 mm from the same shale core or outcrop, then cut the sample into a core sample with a length of 10 mm, measure it with a vernier caliper, flatten and polish both ends of the cylindrical sample, and the base surface deviation at both ends is ≤2.5%.
[0091] The specific test operations are as follows:
[0092] 1) Install the core sample with a permeability of 20 mD according to the operating procedures of the high-temperature and high-pressure wellbore stability simulation experimental device;
[0093] 2) Raise the temperature of the experimental device to the desired temperature of 20°C, 50°C, 80°C, 110°C or 140°C;
[0094] 3) After the temperature is constant, set the confining pressure and axial pressure respectively;
[0095] 4) Inject simulated formation water (200 g / L sodium chloride aqueous solution) upstream and maintain a certain pressure, increase the downstream pressure to maintain a pressure difference of about 1 MPa with the upstream pressure, stop pressurizing, close the downstream inlet, allow the upstream and downstream to reach equilibrium under this pressure difference, and saturate the equilibrium core sample in the simulated formation water;
[0096] 5) After the core sample is saturated, a pore pressure transmission test is performed under the condition that both the upstream and downstream test fluids are simulated formation water. The downstream pressure is measured over time, and the initial permeability K1 of the core sample is recorded;
[0097] 6) Replace the upstream test fluid with the water-based drilling fluid to be tested, and keep the downstream test fluid as simulated formation water (200g / L sodium chloride aqueous solution) to conduct a plugging test. During the test, the pressure difference between the upstream and downstream pressures was maintained at 1MPa, and the test fluid was allowed to react with the core sample for 12 hours;
[0098] 7) After the test fluid has been acting on the core sample for 12 hours, the upstream test fluid is kept unchanged, and the downstream test fluid is kept at a 200 g / L sodium chloride aqueous solution, and a pressure transmission test of the test fluid is performed to determine the change pattern of the downstream pressure over time;
[0099] 8) Output the data and curves recorded in the instrument program, and record the post-plugging permeability K2 when the pressure is balanced. If the downstream pressure has not reached equilibrium after measuring for more than 12 hours, the permeability of the rock sample at the 12th hour is recorded as K2.
[0100] The permeability reduction rate (blocking rate) is calculated based on the following formula:
[0101]
[0102] Where:
[0103] D———permeability reduction rate, %;
[0104] K1——The initial permeability of the core sample, in square micrometers (μm 2 );
[0105] K2——The permeability of the core sample after plugging, in square micrometers (μm 2 ).
[0106] The results are shown in Table 1.
[0107] Table 1
[0108]
[0109] By comparing the blocking effects at lower temperatures of 20 to 50°C in Table 1 above, it can be seen that since Examples 1 to 3 and Comparative Example 3 are all prepared by composites of rigid particles and flexible materials, a better blocking effect is produced than a single flexible material (Comparative Example 1) or a single rigid particle (Comparative Example 2), indicating that composites of rigid particles and flexible materials can improve the blocking effect. However, with the increase in temperature, at high temperatures of 80 to 130°C, the blocking effect of Comparative Example 3 is not further significantly improved, but the permeability reduction rate is maintained at about 72%, which is equivalent to 69.35% at 20°C and 70.27% at 50°C. However, at high temperatures of 80 to 130°C, the permeability reduction rate of Examples 1 to 3 is increased to more than 92%, even as high as 97%, which indicates that AuNPs / PNIPAM and polybutadiene in the composite particles have a synergistic effect at high temperatures of 80 to 130°C. In addition, although the permeability reduction rate of Comparative Examples 1 and 2 at high temperatures of 80 to 130°C is also improved, they both show a significant downward trend at 130°C compared with 110°C. For Comparative Example 1, this is due to the decomposition of polybutadiene at high temperature; for Comparative Example 2, this is due to the decomposition of PNIPAM in AuNPs / PNIPAM at high temperature. However, in Examples 1 to 3, from 110°C to 130°C, the permeability reduction rate not only did not decrease, but increased slightly. This further illustrates that AuNPs / PNIPAM and polybutadiene in the composite particles have a synergistic effect, thereby showing temperature resistance. The combined use of the two makes up for the problem of decreased permeability reduction rate caused by using either alone at higher temperatures.
Claims
1. A plugging agent, whose raw materials include emulsifier, temporary plugging agent, AuNPs / PNIPAM gel composite, monomer, initiator, viscosity agent, dispersant, defoamer, base liquid and optional antifreeze agent.
2. The plugging agent according to claim 1, characterized in that: The emulsifier is 5 to 6 parts by mass, the temporary plugging agent is 5 to 10 parts by mass, the AuNPs / PNIPAM gel complex is 45 to 55 parts by mass, the monomer is 5 to 8 parts by mass, the initiator is 3 to 6 parts by mass, the viscosity agent is 5 to 6 parts by mass, the dispersant is 2 to 3 parts by mass, the defoamer is 1 to 2 parts by mass, the antifreeze agent is 0 to 4 parts by mass, and the base liquid is 10 to 20 parts by mass.
3. The plugging agent according to claim 1, characterized in that: The emulsifier is sodium hydroxypropane sulfonate methacrylate; and / or The temporary plugging agent is a polymer synthesized from butadiene, styrene and 2-acrylamide-2-methylpropane sulfonic acid in a mass percentage of 3:1:
1.
4. The plugging agent according to claim 1, characterized in that: The monomer is butadiene; and / or The initiator is azobisisobutylamidine dihydrochloride.
5. The plugging agent according to claim 1, characterized in that: The thickening agent is xanthan gum; The dispersant is a nano-silicon dioxide dispersion, and the particle size of the nano-silicon dioxide is in the range of 15 to 100 nm. 90 Less than 90nm, solid content 25wt%; The defoamer is a high carbon alcohol fatty acid ester and / or polydimethylsiloxane; The antifreeze agent is ethylene glycol and / or glycerol; The base liquid is water.
6. A method for preparing the plugging agent according to any one of claims 1 to 5, comprising the following steps: 1) mixing an emulsifier with a base liquid to obtain a first mixed liquid; 2) mixing the first mixed liquid with a temporary plugging agent to obtain a second mixed liquid; 3) mixing the second mixed solution with the AuNPs / PNIPAM gel complex to obtain a third mixed solution; 4) mixing the third mixed liquid with butadiene to obtain a fourth mixed liquid; 5) mixing the fourth mixed solution with an initiator to obtain a fifth mixed solution; 6) mixing the fifth mixed liquid with a thickener, a dispersant, a defoaming agent and an antifreeze agent to obtain a sixth mixed liquid; 7) filtering the sixth mixed solution to obtain a filtrate; 8) Drying the filtrate to obtain the plugging agent.
7. The method according to claim 6, characterized in that In step 1), stirring at 30 to 50° C. and 60 to 120 r / min for 5 to 7 min to mix evenly; and / or In step 2) to step 4), the mixture is stirred and mixed at 30 to 50° C. and 4500 to 6000 r / min for 10 to 35 min.
8. The method according to claim 6, characterized in that In step 5), the initiator is added to the fourth mixed solution at 70 to 90° C., and the mixture is reacted at a temperature of 50 to 70° C. and a stirring speed of ≤120 r / min for 25 to 45 min.
9. The method according to claim 6, characterized in that In step 6), the fifth mixed solution is mixed with a thickener, a dispersant, a defoamer and an antifreeze agent under stirring at 50 to 70° C., and stirring is continued at 50 to 70° C. for 1 to 2 hours; and / or In step 8), after the filtrate is stirred for 3 to 5 minutes, the filtrate is dried by vacuum drying at 75 to 85° C. for 8 to 10 hours.
10. Use of the plugging agent according to any one of claims 1 to 5 or the plugging agent prepared by the method according to any one of claims 6 to 9 as a component in a water-based drilling fluid; Preferably, the application is an application for plugging a formation at a formation temperature of 80 to 130°C.